Papusza – From Traitor to Heroine - Krzyżanowski, Piotr J.; Wasilewski, Krzysztof (Journal of Applied Cultural Studies, 2016)
The authors of the article focus the concept of alternative theatre, the Polish alternative theatre experience as a part of universal countercultural movement, the outdoor and site specific theatre festivals as a tool for social change and the future prospects of the alternative theatre in Poland. The term “alternative theatre” assumes the conscious adoption of a critical and rebellious attitude against the existing social and political status quo. What is more, it assumes a desire by artists of the theatre to supplant the existing methods of social communication with other, more creative ways, which better contribute to the self-development of individuals who participate in the process. Here, theatrical performance signifies the wish of theatrical artists to change the structure of their contemporaries’ perception and valorisation of the world.